2009
DOI: 10.1016/j.jinorgbio.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of native calf thymus DNA with FeIII-dipyrido[3,2-a:2′,3′-c]phenazine

Abstract: a b s t r a c tThe mono and bis dipyrido[3,2-a:2 0 ,3 0 -c]phenazine (dppz) adducts of iron(III) chloride, i.e. [Fe(dppz)]Cl 3 and [Fe(dppz) 2 ]Cl 3 , have been synthesized and characterized. The interaction of the Fe III dppz hydrolyzed aquo complex with native calf thymus DNA has been monitored as a function of the metal complex-DNA molar ratio, by variable temperature UV absorption spectrophotometry, circular dichroism (CD) and fluorescence spectroscopy. The results obtained in solution at various ionic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…EB is weakly fluorescent; upon complexation with DNA it emits intense fluorescence light as a consequence of the strong intercalation of EB between adjacent DNA base pairs [68,69]. It has been extensively reported that the enhanced fluorescence of the EB-DNA complex can be quenched by the addition of a second molecule [70,71].…”
Section: Fluorescence Spectroscopic Studiesmentioning
confidence: 99%
“…EB is weakly fluorescent; upon complexation with DNA it emits intense fluorescence light as a consequence of the strong intercalation of EB between adjacent DNA base pairs [68,69]. It has been extensively reported that the enhanced fluorescence of the EB-DNA complex can be quenched by the addition of a second molecule [70,71].…”
Section: Fluorescence Spectroscopic Studiesmentioning
confidence: 99%
“…The dppz ligand was synthesized and characterized as reported [28,54]. [Cu(gly)dppz]ClO 4 (1) (gly = glycinato) was synthesized by modifying a general synthetic method previously reported [33,37].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…4, shows an intense band at 275 nm and a weaker multiplet in the range 340-400 nm, which is the typical infra-ligand (IL) band of coordinated dppz [28]. Such IL band was used to monitor the interaction with DNA, because the latter shows no absorption in such wavelength range.…”
Section: Dna-binding Experimentsmentioning
confidence: 99%
See 2 more Smart Citations